FOREIGN LANGUAGE COMPETENCE OF THE CITIZENS OF POLAND AND CZECH REPUBLIC WITHIN THE CONTEXT OF CURRENT ALL-EUROPEAN LINGUISTIC - Gromov, Yevhen; Kolomiiets, Alla; Lazarenko, Natalia; Zhovnych, Olesia; Biretska, Liliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The comparative analysis of the foreign language competence among the citizens of Poland and Czech Republic has been accomplished. The received findings were compared with current observations of all-European linguistic tendencies. Having analysed various statistics the authors succeeded in assembling the social portrait of an average multilingual European. The authors have also considered the fact that over the past years the official percentage of multilingual citizens, both in Poland and the Czech Republic, has significantly decreased due to intensive emigration processes. In the authors’ opinion, this problem is mostly of the socio-economic nature and demonstrates rather not the weakness of educational systems, but the ability of educational institutions of both countries to prepare competitive specialists who are able (due to the high level of foreign language competence) to find decent job in the labour-market of the United Europe. It has also been stated that since the foreign language competence has become a professional and cultural prerequisite for creation of the unified globalized Europe, and multilingualism has become a part of the European identity, the future specialists’ foreign language training in Ukraine should be conducted precisely taking into account the prospects of European integration.